2022
DOI: 10.1037/sah0000416
|View full text |Cite
|
Sign up to set email alerts
|

Affective, cognitive, and behavioral mental illness stigma in health care: A comparison between general ward nurses and the general population.

Abstract: Stigma from health professionals and the general population can be a barrier in health care for people with mental illness. The aim of this study was to compare experiences with and perceptions of people with mental illness between general ward nurses and the general population in the United Kingdom as well as to examine the associated mechanisms. Participants were general ward nurses (n = 101) and the general population (n = 116) in the United Kingdom who completed a survey for this cross-sectional study. Nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Stigma and discrimination against the mentally ill are widespread even in a population that is expected to be enlightened. There is a need in to develop strategies to change the stigma attached to mental illness at both institutional and community levels [9], [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma and discrimination against the mentally ill are widespread even in a population that is expected to be enlightened. There is a need in to develop strategies to change the stigma attached to mental illness at both institutional and community levels [9], [35].…”
Section: Discussionmentioning
confidence: 99%
“…When talking about the stigma, there is a lack of knowledge about mental illnesses, both in the general population and among health professionals, where prejudices and negative attitudes, and discriminatory behaviors occur, which create a strong driver of social exclusion of people with mental illnesses and a violation of their rights and needs [8], [9]. Studies examining professionals' perceptions of mental illness have found overwhelmingly negative attitudes and approval of restrictive and discriminatory practices toward mentally ill people [10], [11].…”
Section: Introductionmentioning
confidence: 99%